2008
DOI: 10.1007/s10750-008-9297-0
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour, efficiency and food preference in yabbies Cherax destructor

Abstract: The influence of body size on the consumption of live zooplankton (Daphnia spp.) by freshwater crayfish was examined using yabbies (Cherax destructor) ranging from 5 to 45 g. Food preference between live zooplankton and inert pellets was also assessed under experimental conditions. In experimental tanks, yabbies of four size classes (\15, 15-24.9, 25-34.9 and 35-45 g) were presented with live Daphnia. All yabbies were held in separate tanks with five animals per size class. In yabbies less than 15 g, the feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
(17 reference statements)
0
6
2
Order By: Relevance
“…This is in contrast to a study on hatchling P. leniusculus, where no significant difference in survival between Artemia cysts and live Artemia nauplii was observed (González et al, 2009). When four age classes of yabby Cherax destructor were tested with live plankton versus pellet food, they spent 85% of their time feeding on live food and 15% feeding on the inert pellets (Meakin et al, 2008), demonstrating a preference for live food items. This was also observed in a study where juvenile hairy marron Cherax tenuimanus, when presented with both live Daphnia and pellet, showed a significant preference for feeding on the live food (Meakin et al, 2009).…”
Section: Hatchling Survivalcontrasting
confidence: 97%
“…This is in contrast to a study on hatchling P. leniusculus, where no significant difference in survival between Artemia cysts and live Artemia nauplii was observed (González et al, 2009). When four age classes of yabby Cherax destructor were tested with live plankton versus pellet food, they spent 85% of their time feeding on live food and 15% feeding on the inert pellets (Meakin et al, 2008), demonstrating a preference for live food items. This was also observed in a study where juvenile hairy marron Cherax tenuimanus, when presented with both live Daphnia and pellet, showed a significant preference for feeding on the live food (Meakin et al, 2009).…”
Section: Hatchling Survivalcontrasting
confidence: 97%
“…Larger marron were, in fact, able to capture a greater number of zooplankters than smaller conspecifics within the same period of time. As Meakin et al (2008) found that yabbies (Cherax destructor) could easily capture live zooplankton well past the juvenile stage, post juvenile marron 0 4 1-2.9 3-7.9 8-1 5…”
Section: Discussionmentioning
confidence: 99%
“…However. Meakin et al (2008) recently found that the yabby is capable of consuming large quantities of live daphnids beyond the juvenile stage.…”
Section: Introductionmentioning
confidence: 99%
“…New freshwater crayfish culture industries are needed, therefore, to meet a growing demand for product. Three Cherax species (redclaw, C. quadricarinatus ; yabby, C. destructor ; and marron, C. tenuimanus ) have been identified as excellent candidate species for commercial culture (Lawrence & Jones ; Meakin, Qin & Mair ; Wingfield ), and farming systems have been developed for each species over the past two decades (Wingfield ).…”
Section: Introductionmentioning
confidence: 99%